The Effect of Teaching Factory (TEFA) Learning and Entrepreneurial Readiness on the Entrepreneurial Interest of Class XI Culinary Students at SMK 6 Semarang - Pinky Amanda Saputri Manakib; Pudji Astuti (Universitas Negeri Padang, 2026)
This study examined the influence of teaching factory (TEFA) learning and entrepreneurial readiness on the entrepreneurial interest of Grade XI Culinary students at SMK Negeri 6 Semarang. The study employed a quantitative approach using a survey method involving 138 students selected through total sampling. Data were collected using a 1–5 Likert scale questionnaire and analyzed using simple linear regression and multiple linear regression with the assistance of SPSS version 27. Prior to hypothesis testing, the regression model fulfilled the classical assumption tests, including normality, linearity, multicollinearity, and heteroscedasticity tests, indicating that the model was appropriate for further analysis. The results revealed that teaching factory (TEFA) learning had a positive and significant effect on entrepreneurial interest, with a regression coefficient of 0.374 and a significance level of <0.001. Entrepreneurial readiness also showed a positive and significant effect, with a regression coefficient of 0.451 and a significance level of <0.001. Simultaneously, both variables significantly influenced entrepreneurial interest, as indicated by the F-value of 83.129 with a significance level of <0.001. The adjusted coefficient of determination (Adjusted R²) value of 0.552 indicated that 55.2% of the variance in entrepreneurial interest could be explained by teaching factory (TEFA) learning and entrepreneurial readiness, while the remaining 44.8% was influenced by variables outside the scope of this study. This study was limited to Grade XI Culinary students at SMK Negeri 6 Semarang and only examined two independent variables related to entrepreneurial interest. In addition, the results of the classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests, demonstrated that the regression model met the required analytical assumptions.